An ACO-based Routing Algorithm for Multimedia CDN Networks - Chen, Jian-Bo; Wang, Yui-Lin (Proceedings of Engineering and Technology Innovation, 2015)
Multimedia Content Delivery Networks is used to distribute multimedia contents from origin server to many replica servers, which can reduce the loads and can improve the availability. The client request must be redirected to the most appropriate one among these replica servers. In this paper, we proposed Ant Colony Optimization (ACO) based routing algorithm to solve this problem. The ants in ACO-based routing algorithm will release pheromone when they go through the path. The routing decision is based on the cumulative pheromone of the path. The ACO-based routing algorithm not only can find the most appropriate path but also can suit for dynamic topology. When the topology changes frequently, the ACO-based routing algorithm will always find a optimized path. The simulation results show that the ACO-based routing algorithm can achieve higher performance than the other mechanisms.